2012
DOI: 10.1371/journal.pone.0046691
|View full text |Cite
|
Sign up to set email alerts
|

Statin Use and Risk of Prostate Cancer: A Meta-Analysis of Observational Studies

Abstract: BackgroundEmerging evidence suggests that statins may decrease the risk of cancers. However, available evidence on prostate cancer (PCa) is conflicting. We therefore examined the association between statin use and risk of PCa by conducting a detailed meta-analysis of all observational studies published regarding this subject.MethodsLiterature search in PubMed database was undertaken through February 2012 looking for observational studies evaluating the association between statin use and risk of PCa. Before met… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

15
162
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 184 publications
(179 citation statements)
references
References 53 publications
15
162
0
Order By: Relevance
“…Previous studies have shown that statins can prolong survival, while others have reported no benefits in cancer patients (1). Concerning prostate cancer, the anticancer effect of statins is controversial (2,3). We previously reported that statins inhibit prostate cancer progression via suppressing the expression of insulin-like growth factor 1 receptor (IGF1R) and increasing ANXA10 (4,5).…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have shown that statins can prolong survival, while others have reported no benefits in cancer patients (1). Concerning prostate cancer, the anticancer effect of statins is controversial (2,3). We previously reported that statins inhibit prostate cancer progression via suppressing the expression of insulin-like growth factor 1 receptor (IGF1R) and increasing ANXA10 (4,5).…”
Section: Introductionmentioning
confidence: 99%
“…12) Epidemiological studies have shown a reduced risk of advanced prostate cancer with the use of statins. [13][14][15][16] Statin use was also found to be associated with a reduction in the risk of biochemical recurrence in patients with prostate cancer 17) and a decreased risk of cancer mortality. 18) Recent studies have shown statin drugs including atorvastatin (Lipitor ® ) inhibit proliferation and induce apoptosis of prostate cancer cells.…”
mentioning
confidence: 98%
“…In addition, statins exert proapoptotic, antiangiogenic, and immunomodulatory effects, which may prevent cancer growth [1,2] . Indeed, several observational studies and meta-analyses have shown that statin use may be associated with reduced risk of prostate cancer [3] , hepatocellular cancer [4] , gastric cancer [5] and esophageal cancer [6] but not others [7,8] . More recently, there has been greater interest in the potential role of statins in modifying cancer outcomes and mortality.…”
Section: Statins and Cancer Mortalitymentioning
confidence: 99%